p18 encoded by FgGMTV1 is responsible for asymptomatic infection in Fusarium graminearum - Lihang Zhang; Pengfei Li; Yanfei Wang; Shuangchao Wang; Lihua Guo (mBio)
ABSTRACT The intricate interplay between mycoviruses and their fungal hosts frequently culminates in asymptomatic infections, but the virus-derived factors underlying these infections remain poorly understood. Our study introduces p18, a novel protein encoded by the DNA-C segment of the genomovirus FgGMTV1, which facilitates the transition from virus-induced hypovirulence to asymptomatic infection within Fusarium graminearum upon its expression. We have confirmed the expression of p18 during FgGMTV1 infection and observed its presence in both the nucleus and cytoplasm. Remarkably, strains with a p18 null mutation show a significant reduction in colony expansion, conidial production, and virulence, leading to a hypovirulent phenotype. Our results also indicate that p18 hinders the accumulation of FgGMTV1, thus determining asymptomatic infection and enabling vertical transmission through conidia. Furthermore, the p18 null mutant virus converts F. graminearum from virulent to hypovirulent strains on wheat leaves after horizontal transmission. This work not only expands our knowledge of the genomovirus proteome but also provides insights into the strategies of viral evolution and adaptation. Moreover, we propose an innovative approach for creating hypovirulent strains utilizing engineered mycoviruses for the biocontrol of plant pathogenic fungi.IMPORTANCEMycovirus-fungus interplay often leads to asymptomatic infections. Our study identifies p18, a novel protein from the genomovirus FgGMTV1, as a key determinant of asymptomatic infection in Fusarium graminearum. A p18-null mutant exhibits a pronounced hypovirulent phenotype. By modulating viral accumulation, p18 promotes asymptomatic infection and facilitates vertical transmission via conidia. This insight deepens our understanding of mycovirus-fungus interactions and introduces a novel strategy for biocontrol using engineered mycoviruses.